2021
DOI: 10.3390/jcm10194430
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Molecular Mechanisms Underlying Cardiac Fibrosis and Atrial Fibrillation

Abstract: The cellular and molecular mechanism involved in the pathogenesis of atrial fibrosis are highly complex. We have reviewed the literature that covers the effectors, signal transduction and physiopathogenesis concerning extracellular matrix (ECM) dysregulation and atrial fibrosis in atrial fibrillation (AF). At the molecular level: angiotensin II, transforming growth factor-β1, inflammation, and oxidative stress are particularly important for ECM dysregulation and atrial fibrotic remodelling in AF. We conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 128 publications
0
44
0
Order By: Relevance
“…CFs are also the predominant source of matrix metalloproteinases (MMPs), which are calcium-dependent zinc-containing endopeptidases responsible for matrix protein degradation. MMPs are involved in collagen deposition and pro-fibrotic signaling and are important for cardiovascular diseases [ 39 ]. MMPs are tightly regulated by an endogenous group of inhibitors known as tissue inhibitors of metalloproteinases (TIMPs) [ 40 ].…”
Section: Cardiac Ecm Characteristics and Homeostasismentioning
confidence: 99%
“…CFs are also the predominant source of matrix metalloproteinases (MMPs), which are calcium-dependent zinc-containing endopeptidases responsible for matrix protein degradation. MMPs are involved in collagen deposition and pro-fibrotic signaling and are important for cardiovascular diseases [ 39 ]. MMPs are tightly regulated by an endogenous group of inhibitors known as tissue inhibitors of metalloproteinases (TIMPs) [ 40 ].…”
Section: Cardiac Ecm Characteristics and Homeostasismentioning
confidence: 99%
“…Particularly, atrial interstitial fibrosis seems to be the key factor contributing to AF development [45]. It is known that left atrial (LA) interstitial fibrosis plays a significant role in initiating and maintaining atrial fibrillation [45,46]. Galectin-3 enhances cardiac fibrosis and remodelling and is a well-documented cause of arrhythmia.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…They enhance AF substrate formation and contribute to contractile dysfunction, atrial electrical, and structural remodeling in AF. 29 Clinical studies indicated that some nutrition-related factors were implicated in AF-related inflammation and oxidative stress. Group B vitamins, including vitamin B12, were shown to be linked with circulating levels of C-reactive protein, homocysteine (Hcy), and matrix metalloproteinases, which are important contributors to the development of AF.…”
Section: Discussionmentioning
confidence: 99%